THE EFFECTIVENESS OF IMPLEMENTING AN ERP SYSTEM FOR RAW MATERIAL (Case Study at PT. Pharmacy) - Taufanti, Salsabila; Rahayu, Viera Sree; Effendi, Moch Irsyad; Indria, Nurtika; Agustinus, Rainer; Christina, Veronica (CENTRAL ASIA AND THE CAUCASUS, 2022)
Inventory is an asset of great value in a company, the ineffectiveness of inventory management will cause problems for the company. This study is intended to evaluate the effectiveness of implementing Enterprise Resources Planning (ERP) in order to find solutions to problems faced by pharmaceutical companies that have very large types and quantities of inventory. This research is a descriptive study, by collecting data using questionnaires distributed to ERP users as well as conducting observations and interviews. The results showed that the ERP applied to the company was effective in terms of system quality, information quality, service quality, user satisfaction, and employee performance.